An investigation of thermal behaviour of biomass and coal during co‐combustion using thermogravimetric analysis (TGA). (15th July 2013) - Vhathvarothai, Navirin; Ness, James; Yu, Jimmy
SUMMARY The thermal behaviour and kinetic analysis of biomass (cypress wood chips and macadamia nut shells) and Australian bituminous coal during combustion were studies using the thermogravimetric technique with four different heating rates under an air atmosphere. Each type of biomass was blended with coal at mass ratios (biomass:coal) of 95:5, 90:10, 85:15 and 80:20 to investigate the effect of coal as a supplementary fuel on thermal behaviour during the combustion process. Combustion of the individual samples and the blends took place in three steps comprising dehydration, devolatilisation and char oxidation. During co‐combustion, the thermal decomposition behaviour of the blends followed that of the weighted average of the individual samples in the blends. In kinetic analysis, thermal decomposition of biomass and coal appeared to take place independently, and thus, the activation energy of the blends can be calculated from that of the two components. No evidence for any significant synergetic effects or thermal interaction was found between either type of biomass and the coal during co‐combustion based on the lack of deviation from expected behaviour of the blends. Copyright © 2013 John Wiley & Sons, Ltd.